Critical Evaluation of Specific Efficacy of Preparations Produced According to European Pharmacopeia Monograph 2371 - Annekathrin Ücker; Stephan Baumgartner; David Martin; Tim Jäger (Biomedicines, 2022)
European Pharmacopoeia monograph 2371 describes the production of homeopathic preparations. A specific efficacy of these preparations in high dilution levels is questionable in view of basic scientific principles. There is empirical evidence for such effects, for example in a Lemna-intoxication bioassay published 2010. To test the replicability and robustness of this bioassay, we conducted two experimental series (five independent blinded and randomised experiments each). The specimen of Lemna gibba L., clone-number 9352, were stressed in arsenic solution for 48 h (158 mg/L AsNa2HO4 (250 mg/L in series 2)), then grew in either As2O3 preparations produced according to Eu. Pharm. Monogr. 2371 or control solution. Comparing the area-related relative growth rate of day 3–9 (rgr 3–9) between treatment and control groups for each series showed differences that were not significant in series 1 (p = 0.10), significant in series 2 (p = 0.04) and significant in the pooled data of both series (p < 0.01). The effect direction (rgr 3–9 increase) was comparable to experiments of 2010, but the effect size was smaller, likely due to a changed light cycle. These results are not compatible with the hypothesis that the application of European Pharmacopoeia monograph 2371 results in pharmaceutical preparations without specific effects. Further studies are needed to investigate a potential mode of action explaining these effects.